Haplopteris yakushimensis (Pteridaceae, Vittarioideae), a new species from Yakushima Island, Japan - Chen, Cheng-Wei; Ebihara, Atsushi; Chiou, Wen Liang; Li, Chia Wei (Phytotaxa, 2014)
A new species of vittarioid ferns (Pteridaceae) that has long been regarded as Haplopteris amboinensis or H. forrestiana (a synonym of H. doniana), is described here as Haplopteris yakushimensis. Both macro- and micromorphological characteristics were compared with these two species. Chartaceous matured fronds, shallowly grooved adaxial costae and obtuse carinate abaxial costae are the diagnostic characteristics that distinguish H. yakushimensis from the other species in the genus. A phylogeny based on plastid regions chlL, ndhF and matK of 14 East-Asian Haplopteris species, including our new taxon is presented here.